A Perovskite Photodetector Crossbar Array by Vapor Deposition for Dynamic Imaging. Issue 51 (10th November 2022) - Zhan, Zhenye; Lin, Dongxu; Cai, Juntao; Lu, Yueheng; Chen, Aidi; Zhang, Tiankai; Chen, Ke; Liu, Pengyi; Wang, Xiaomu; Xie, Weiguang
Abstract: With the development of perovskite photodetectors, integrating photodetectors into array image sensors is the next target to pursue. The major obstacle to integrating perovskite photodiodes for dynamic imaging is the optoelectrical crosstalk among the pixels. Herein, a perovskite photodiode–blocking diode (PIN‐BD) crossbar array with pixel‐wise rectifying property by the vapor deposition method is presented. The PIN‐BD shows a large rectification ratio of 3.3 × 10 2 under illumination, suppressing electrical crosstalk to as small as 8.0% in the imaging array. The fast response time of 72.8 ns allows real‐time image acquisition by over 25 frames per second. The imaging sensor exhibits excellent imaging capability with a large linear dynamic range of 112 dB with 4096 gray levels and weak light sensitivity under 1.2 lux. Abstract : A perovskite photodiode–blocking diode crossbar array with pixel‐wise rectifying property by vapor deposition method is presented, which shows a large rectification ratio and suppresses electrical crosstalk in the imaging array. Its fast response time allows smooth real‐time image acquisition. The imaging sensor exhibits excellent imaging capability with a large linear dynamic range and is sensitive to weak light.